East Asian Low Marriage and Birth Rates: The Role of Social Status Affordance in Marriage and Childbearing Behavior - YONG, Jose C. (Institutional Knowledge at Singapore Management University, 2014)
Although declines in marriage and birth rates are generally associated with industrialization and economic advancement, countries with a dominantly East Asian cultural population exhibit the lowest marriage and birth rates in the developed world. This study aims to identify and verify a new latent construct, social status affordance, as an underlying account for the differences in long-term mating outcomes (i.e., marriage and childbearing) between developed East Asian countries and other developed countries. Drawing on an understanding of the specific East Asian cultural values of harmony and deference and, subsequently, the importance of social status conferred by educational and occupational prestige as a means of demonstrating worth and exerting influence while minimizing social confrontations and conflict, this study argues that sufficiently prestigious jobs are therefore more valued and more scarce in developed East Asian countries compared to other developed countries. The dynamic created by such competition for scarce prestigious jobs leads to the perception of less jobs available that are sufficiently prestigious, which leads to overall lower social status affordance in developed East Asian countries. As social status is valued as a trait that enables life outcomes, including mating goals, lower social status affordance may underlie lower marriage and birth rates in developed East Asian countries. The results, to a larger extent, support the propositions of this study, and suggestions for East Asian countries facing low marriage and birth rates are made given the implications of the findings obtained.